Supernatural Powers And Human Struggles In Stephen King’s “Doctor Sleep” - pcadmin, Ulugbek Ochilov (Zien Journals, 2025)
Scholars have given King little notice as a writer of magical realism as a narrative strategy. In this article highlights of supernatural powers and human struggles in Stephen King’s “Doctor sleep”.
Keywords: human struggles; supernatural powers; Doctor sleep; Stephen King